JUDGE VERDICTS ON SUBSIDIARY FINE PENALTY OF CORRUPTION CRIMES (A Case Study on High Prosecutor General Office of NTT) - Sulistyanta Sulistyanta; Henderina Malo (Faculty of Law, Universitas Jenderal Soedirman, 2017)
Additional fine penalty in corruption constitutes specific regulation. This aims to restore the state financial loss and to give deterrent effect. Yet, the judge's verdict raises problems: Why do the judge's verdicts related to subsidiary fine penality by imprisonment penalty tend to vary and inconsistent in length of the imprisonment. The purpose of the study is to identify and analyze the judge's consideration in determining various and inconsistent subsidiary fine penalty by imprisonment. The research applied normative juridical method by relying on primary and secondary legal materials. The results show that: 1) judges do not specifically regulate fine penalty or subsidiary in terms of imprisonment penalty. The large amount of fine penalty does not equal to the relatively short imprisonment which does not result in a deterrent effect. 2) There is no limit to the length of imprisonment for a short sentence. Thus, it is suggested that proportional regulation is required between fine penalty and imprisonment penalty subsidiary for restoring state financial loss.Keywords: fine penalty, imprisonment penalty subsdiary, judge's verdict